A review of data collection practices using electromagnetic articulography. Issue 1 (1st March 2021) - Rebernik, Teja; Jacobi, Jidde; Jonkers, Roel; Noiray, Aude; Wieling, Martijn
Abstract : This paper reviews data collection practices in electromagnetic articulography (EMA) studies, with a focus on sensor placement. We first introduce electromagnetic articulography as a method. We then focus on existing data collection practices. Our overview is based on a literature review of 905 publications from a large variety of journals and conferences, identified through a systematic keyword search in Google Scholar. The review shows that experimental designs vary greatly, which in turn may limit researchers' ability to compare results across studies. Finally, we describe an EMA data collection procedure that includes an articulatory-driven strategy for determining where to position sensors on the tongue without causing discomfort to the participant. We also evaluate three approaches for preparing (NDI Wave) EMA sensors reported in the literature with respect to the duration the sensors remain attached to the tongue: 1) attaching out-of-the-box sensors, 2) attaching sensors coated in latex, and 3) attaching sensors coated in latex with an additional latex flap. Results indicate no clear general effect of sensor preparation type on adhesion duration. A subsequent exploratory analysis reveals that sensors with the additional flap tend to adhere for shorter times than the other two types, but that this pattern is inverted for the most posterior tongue sensor.